Louvor e ação social: estudo sobre a Renovação Carismática Católica e a Associação Servo de Deus em Goiânia - Neta, Maria dos Santos Pimentel (2019)
This work had as object of investigation the Catholic Charismatic Renewal (RCC) in Goiania and its social actions through the Servant of God Association (ASD), mainly regarding the influence of the CCR for the society of Goiás. The focus of the research is the charismatic Catholic movement, called Catholic Charismatic Renewal. The theoretical references to support the studies were based on the framework of the Social Sciences and Sciences of Religion that have supported reflections and analysis about the charismatic Catholic religious phenomenon. For the accomplishment of this study the bibliographical revision of exploratory nature was used, for the development and the considerations we used the inductive method. During the study we found that prayer groups, which are the mainstay of the CCR, can be quite distinct from each other as well as the clerical leaderships who support it. the layman's intimate experience with the sacred.